2003
DOI: 10.1002/da.10130
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and anxiety: Subtle and obvious attributes of abuse in adults with social anxiety disorder and panic disorder

Abstract: Previous research has found a relation between social anxiety disorder and alcoholism but recent work found no differences in drinking levels among socially anxious individuals, dysthymics, and normal controls. Using a more sophisticated measure of substance abuse may further explicate the relation between social anxiety and drinking. We examined aspects of substance abuse in treatment-seeking individuals with social anxiety disorder or panic disorder (psychiatric control group) as well as nondisordered indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
4
0
2
Order By: Relevance
“…Independent studies also suggest that SASSI scores and classifications are influenced substantially by general distress and deviance. Positive relationships with SASSI scales have been reported for conduct disorder [38], depression [19,20,38], social anxiety [16], general distress and traumatic histories [19,22], and suicidal ideation or attempts [39,41]. The indirect scales and associated decision rules seem particularly linked to more global distress and psychopathology [16,30,46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Independent studies also suggest that SASSI scores and classifications are influenced substantially by general distress and deviance. Positive relationships with SASSI scales have been reported for conduct disorder [38], depression [19,20,38], social anxiety [16], general distress and traumatic histories [19,22], and suicidal ideation or attempts [39,41]. The indirect scales and associated decision rules seem particularly linked to more global distress and psychopathology [16,30,46].…”
Section: Resultsmentioning
confidence: 99%
“…The 36 located studies and two SASSI manuals spanned a wide variety of samples. The adult studies included college students [11–17], pregnant women [9,18–21], mothers of young children [22], community residents [3,13], members of Alcoholics Anonymous [23–26], couples [27], people with traumatic brain injury [28–30] and adults in addiction treatment [3,13,25,26,31], psychiatric settings [3,13,16], correctional programs [3,13,32–34] and welfare or child protective services [9,19,35]. The adolescent studies comprised samples from community or high school [23,36–40], substance abuse [4,23,38,41,42], psychiatric in‐patient [4,38,42–44] and correctional settings [4,34,38,42,44–46].…”
Section: Methodsmentioning
confidence: 99%
“…En psicología social se han realizado esfuerzos por explicar el consumo excesivo de alcohol. Se ha observado que la ansiedad social y los desórdenes ligados a la misma (por ejemplo, temor a la evaluación social negativa) se asocian con un mayor consumo de alcohol en personas adultas (Ham, Debra & Hope, 2003;Ham, Hope, White & Rivers, 2002). Otro trastorno ligado al consumo de alcohol es la depresión, el consumo excesivo se relaciona con mayores índices de depresión (Lukassen & Beaudet, 2005;Echeburúa, 2001).…”
unclassified
“…In a study examining alcohol expectancies, Ham, Hope, White and Rivers (2002) found no differences in the amount of alcohol consumed among individuals with social anxiety, dysthymia, and control group. However, when the same researchers used a more sensitive scale designed to measure both the obvious and subtle aspects of substance abuse, researchers found that individuals who were socially anxious endorsed more substance use items than those in the panic disorder or control groups (Ham & Hope, 2003). Thus, although there have been some contradictory findings, social anxiety has been demonstrated to co-occur with substance use, particularly alcohol use disorders (Buckner et al, 2006; Kushner et al, 1990; Ham & Hope, 2003; Van Armegian Mancini, Styan & Donisan, 1991).…”
mentioning
confidence: 99%